(3GdQjGVjGJ HfjJgG GdeYQajI hGSJQGJjLjGJ JOQjSgGs - (3aDGO eMeO(B, (3ehSis ((3GdEScfOQjI(B:s (3OGQ hecJHI GdESQGA(B,s, 2005)
(3jVe WHjYI GdQjGVjGJ heMJhjGJ eGOI GdQjGVjGJ, GdCgOGa GdYGeI dJOQjS GdQjGVjGJ, GdCgOGa GdSdhcjI deGOI GdQjGVjGJ, GSJQGJjLjGJ GdJOQjS, NWhGJ GdJOQjS, GSJQGJjLjI JMbjb GdgOa GdChd, GSJQGJjLjI JMbjb GdgOa GdKGfj, GSJQGJjLjI JMbjb GdgOa GdKGdK hGSJQGJjLjI JMbjb GdgOa GdQGHY, GSJQGJjLjI JMbjb GdgOa GdNGeS , GSJQGJjLjI JMbjb GdgOa GdSGOS, GSJQGJjLjI JMbjb CgOGa JOQjS GdegGQGJ, GSJQGJjLjI GdCSFdI GdTahjIs
(3GdeQGLY U(B.281s
Keywords: (3GdQjGVjGJs; (3GdQjGVjGJ(B- (3JYdje hJOQjSs